A high heat-insulating refractory material for lightweight bricks and preparation method thereof

By using raw materials such as calcined alumina, wollastonite, expanded perlite and ceramics, combined with soy protein foaming agent and natural polymer materials, high heat insulation and refractory materials for lightweight bricks are prepared, which solves the problems of high density, strong thermal conductivity and insufficient flexural strength of traditional refractory materials, and achieves high-efficiency heat insulation and refractory properties.

CN119285341BActive Publication Date: 2025-03-07SHANDONG WEINAI ENERGY-SAVING MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411802926.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

Traditional refractory materials have high density, strong thermal conductivity and insufficient flexural strength, making it difficult to meet the heat insulation and refractory needs in high temperature environments.

Method used

The high-thermal insulation refractory materials for light bricks are prepared by optimizing the process by combining soy protein foaming agent and natural polymer materials.

Benefits of technology

It significantly improves the insulation performance, strength and fire resistance of the material, reduces density and thermal conductivity, and is suitable for heat insulation and fire resistance requirements in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of new materials, and discloses a high-insulation refractory material for lightweight bricks and a preparation method thereof, the preparation method comprising: mixing calcined alumina, wollastonite, expanded perlite and ceramsite to obtain an aggregate mixture; dissolving a soy protein foaming agent, adding sodium alginate and polyvinyl alcohol, and stirring to obtain a foaming solution; mixing the foaming solution with the aggregate mixture, and sequentially adding aluminum fluoride, hydrated bauxite powder, nano-scale silicon dioxide powder and activated carbon powder during the stirring process, stirring until uniform, and preparing a foam slurry; pouring the foam slurry into a mold for molding, and then performing low-temperature drying to obtain a material to be fired; finally, firing the material to be fired to obtain a high-insulation refractory material for lightweight bricks. The present invention significantly improves the performance of the refractory material by introducing a soy protein foaming agent and a natural polymer material, and has excellent thermal insulation, low thermal conductivity, high strength and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a high heat-insulating refractory material for lightweight bricks and a preparation method thereof. Background Art

[0002] With the advancement of industrialization, the application of refractory materials in high-temperature environments such as metallurgy, electricity, chemical industry, and construction has become increasingly important. Especially in environments with high temperature, high pressure, and drastic temperature fluctuations, refractory materials not only need to have high strength and high heat resistance, but also good thermal insulation performance. Although traditional refractory materials have excellent performance in strength and heat resistance, they usually have problems such as high density, strong thermal conductivity, and insufficient flexural strength. Therefore, the development of new lightweight and highly insulating refractory materials, especially materials with good thermal insulation performance, low density, high strength, and low thermal conductivity, has become a hot topic in current refractory research.

[0003] Traditional refractory materials, such as bauxite and refractory clay bricks, can effectively maintain their structural stability at high temperatures and are widely used in metallurgy, ceramics and steel industries. However, these materials are usually dense, heavy and have high thermal conductivity, making them unsuitable for applications that require good thermal insulation. At the same time, most traditional refractory materials lack sufficient toughness and are prone to brittle cracking, resulting in breakage during use and shortened service life.

[0004] Therefore, it is now urgent to invent a refractory material that can solve the above problems. Summary of the invention

[0005] In view of this, the present invention proposes a high thermal insulation refractory material for lightweight bricks and a preparation method thereof, aiming to effectively improve the thermal insulation performance of the material and enhance its strength and fire resistance by introducing innovative raw materials and optimizing the process.

[0006] The present invention provides a method for preparing a high heat-insulating refractory material for lightweight bricks, comprising:

[0007] Mixing calcined alumina, wollastonite, expanded perlite and ceramsite to obtain an aggregate mixture;

[0008] After dissolving the soy protein foaming agent, sodium alginate and polyvinyl alcohol are added, and the foaming solution is obtained after stirring;

[0009] The foaming solution and the aggregate mixture are mixed and stirred, and aluminum fluoride, hydrated bauxite powder, nano-scale silicon dioxide powder and activated carbon powder are added during the stirring process, and the foam slurry is obtained after stirring evenly;

[0010] The foam slurry is cast and then dried at low temperature, and then subjected to constant temperature treatment at 300±20° C. to obtain a material to be fired;

[0011] The material to be fired is fired to obtain the high heat-insulating refractory material for lightweight bricks.

[0012] Preferably, the weight ratio of the calcined alumina, wollastonite, expanded perlite, ceramsite, soy protein foaming agent, sodium alginate, aluminum fluoride, hydrated bauxite powder, nano-silicon dioxide, activated carbon powder and polyvinyl alcohol is 25-35:20-30:10-18:5-10:4-7:4-5:3-5:6-10:2.5-4:2-3.5:2-3.

[0013] Preferably, the preparation method of the soy protein foaming agent comprises:

[0014] The red algae polysaccharide is dissolved in water to obtain a polysaccharide solution; after the soybean protein and the polysaccharide solution are mixed, glycerol monostearate is added, and after the mixture is evenly mixed, nano-scale silicon dioxide powder is added for shear mixing to obtain the soybean protein foaming agent.

[0015] Preferably, the weight ratio of the soy protein, red algae polysaccharide, glycerol monostearate and nano-scale silicon dioxide powder is 50-70:1-3:1-2:0.5-2.

[0016] Preferably, in the shear mixing, the shear speed is 3000-6000 rpm, the shear time is 3-10 minutes, and the solution temperature is 40-60°C.

[0017] Preferably, the red algae polysaccharide is laver.

[0018] Preferably, the concentration of sodium alginate is 5%.

[0019] Preferably, when the material to be fired is fired, the firing temperature is 1250-1350°C.

[0020] The present invention also proposes a high thermal insulation refractory material for lightweight bricks, and the high thermal insulation refractory material for lightweight bricks is prepared according to the above-mentioned preparation method of the high thermal insulation refractory material for lightweight bricks.

[0021] The present invention also proposes an application of the above-mentioned high heat-insulating refractory material for lightweight bricks in the preparation of refractory building materials.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. Improved environmental protection and sustainability

[0024] The present invention uses soy protein as a foaming agent, and soy protein is a renewable plant material, does not contain toxic substances, and meets the current requirements for environmental protection. Compared with traditional chemical foaming agents (such as petroleum-based foaming agents), soy protein foaming agents not only reduce environmental pollution, but also avoid the use of non-renewable resources, which helps promote green chemistry and sustainable development.

[0025] 2. Improved foam structure stability

[0026] The stability of the foam is significantly improved by introducing additives such as red algae polysaccharide (porphyrin) and glycerol monostearate. These natural polymer materials can enhance the strength of the foam film during the foaming process, prevent bubbles from bursting, and ensure that the foam structure remains stable during the firing process. Compared with traditional foaming technology, the foam of the present invention is more uniform and long-term stable, greatly improving the overall quality of the material.

[0027] 3. Lower thermal conductivity and better thermal insulation performance

[0028] The present invention uses expanded perlite, ceramsite and other lightweight aggregates, combined with soybean protein foaming agent, to form more pores and microporous structures in the material. These microporous structures effectively reduce the heat conduction path, thereby significantly reducing the thermal conductivity (i.e. thermal conductivity) of the material. Test results show that compared with traditional refractory materials, the foamed lightweight refractory material has lower thermal conductivity, exhibits better thermal insulation, and can adapt to applications requiring high temperature thermal insulation.

[0029] 4. Enhanced material strength and fire resistance

[0030] The strength and thermal stability of the refractory material are improved by adding reinforcing materials such as aluminum fluoride, nano-silicon dioxide and hydrated bauxite powder. The addition of aluminum fluoride regulates the crystal growth during sintering and improves the sintered density, while nano-silicon dioxide and hydrated bauxite powder enhance the mechanical properties and high temperature resistance of the material. The use of these reinforcing ingredients effectively improves the compressive strength, flexural strength and high temperature performance of the material, ensuring its long-term stability in harsh high temperature environments.

[0031] 5. Low density and light weight

[0032] By using light aggregates such as expanded perlite and ceramsite, a good pore structure is formed in the material, which significantly reduces the overall density of the product. Compared with traditional high-density refractory materials, the light refractory material of the present invention is not only light in weight, but also more convenient in construction and transportation, greatly reducing energy consumption and transportation costs, and meeting the needs of the modern construction industry for light and efficient thermal insulation materials.

[0033] 6. Lower production costs

[0034] The raw materials (such as soybean protein, expanded perlite, etc.) used in the present invention are widely available and low in cost. Compared with the high-priced raw materials (such as bauxite, white corundum, etc.) in traditional refractory materials, the production cost of the present invention is relatively low. Therefore, the lightweight high-insulation refractory material of the present invention has good economic efficiency while ensuring performance, and is suitable for large-scale application.

[0035] 7. Improve the versatility of materials

[0036] The refractory material of the present invention not only has good thermal insulation and fire resistance, but also can further adjust the mechanical properties and thermal properties of the material by adjusting the raw material ratio, the amount of foaming agent used, the firing temperature and other process parameters, so as to make the material more flexible and meet the needs of different application scenarios. The material can be widely used in metallurgy, electricity, construction and other fields, and has good market prospects.

[0037] 8. The processing is simple and the process is controllable

[0038] The present invention adopts a mixing process of a soybean protein foaming agent and a traditional refractory aggregate. The foaming process can be controlled by high shear stirring, the stirring time and temperature can be precisely adjusted, the production process is simple, and it is easy to realize industrial production. Compared with some traditional composite materials, the process flow of the present invention is relatively simple, and it is easier to realize large-scale application in industrial production.

[0039] In summary, compared with the prior art, the present invention not only solves the environmental protection problem, but also significantly improves the performance of refractory materials by introducing soybean protein foaming agents and natural polymer material additives, and has excellent thermal insulation, low thermal conductivity, high strength and high temperature resistance, and has low production costs and good market application prospects. Therefore, the present invention has a wide range of application value and potential, and is suitable for thermal insulation and refractory needs in a variety of high temperature environments.

[0040] Principle and mechanism exploration:

[0041] 1. The working principle of foaming agent (soy protein foaming agent)

[0042] Principle: Protein structure and foam stability: Soy protein foaming agent improves the lightness and thermal insulation of refractory materials by forming a foam structure. The colloidal solution formed by soy protein dissolving in water can stably capture air and form tiny and uniform bubbles under mechanical stirring or ultrasonic waves. Since soy protein has rich amino and carboxyl functional groups, it can form a strong interfacial active film on the surface, which helps to improve the stability of the foam.

[0043] Bubble enhancement and dispersion: The air introduced during the foaming process forms a uniform bubble structure in the foam through the interface of soy protein. The smaller the bubble size, the more uniform the foam, the lower the density of the material, and the stronger the thermal insulation. Nano-scale silica particles are used as a skeleton material to fill the foam microstructure, which not only enhances the mechanical strength of the foam, but also further improves the stability of the foam and prevents the foam from breaking during the firing process.

[0044] Microscopic mechanism: The foam structure formed by the soy protein foaming agent provides a large number of micropores for the material at the microscopic level. Air fills these micropores as a low thermal conductivity medium, significantly reducing the thermal conductivity of the material. The air in the foam structure has low thermal conductivity, effectively isolating the transfer of heat energy and enhancing the thermal insulation performance of the material.

[0045] 2. The working principle of aluminum fluoride

[0046] Principle: Sintering promotion and crystal structure control: Aluminum fluoride (AlF3) as a sintering promoter can regulate the crystal growth of the material during high-temperature sintering. Aluminum fluoride can combine with aluminum ions in bauxite during sintering to form aluminum-fluoride compounds with a certain melting point and fluidity, which helps to reduce crack formation during sintering and improve the uniformity of the crystal.

[0047] Microscopic mechanism: During high-temperature sintering, aluminum fluoride reduces the sintering temperature and temperature gradient, promotes the melting and flow of materials such as bauxite and wollastonite, thereby accelerating the rearrangement and tight bonding of the crystal structure, and preventing cracks or stress concentration caused by excessive temperature differences. Ultimately, the addition of aluminum fluoride keeps the porosity of the material at a low level, enhancing its refractoriness and crack resistance.

[0048] 3. The mechanism of action of sodium alginate

[0049] Principle: Foam stabilization and gelation: Sodium alginate (or laver) is a natural polysaccharide that can form a high-viscosity solution in water. Adding sodium alginate can improve the stability of the foam and prevent it from breaking or collapsing. The molecular structure of sodium alginate has strong hydrophilicity and can form strong hydrogen bonds with water molecules, increasing the surface tension of the foam bubbles and thus enhancing the foam's ability to resist compression.

[0050] Microscopic mechanism: During the foaming process, sodium alginate molecules form a gel structure through cross-linking, which reinforces the "shell" of the foam at the microscopic level, making the bubbles more stable and less likely to break. At the same time, the viscosity of sodium alginate also helps to improve the stability of the material at high temperatures, reduce the volume expansion when water evaporates, and thus prevent the material from deforming during the firing process.

[0051] 4. The working principle of expanded perlite and ceramsite

[0052] Principle: Lightweight and thermal insulation: As lightweight aggregates, expanded perlite and ceramsite have significantly low density and excellent thermal insulation. During the high-temperature sintering process, these materials can form a looser porous structure due to the large number of tiny pores, thereby reducing the volume density of the overall material. Their pores are filled with air, which effectively isolates heat transfer and improves the thermal insulation performance of the material.

[0053] Microscopic mechanism: Expanded perlite and ceramsite expand during the sintering process, forming a porous structure. At the microscopic level, they provide a large number of tiny bubbles or pores, which effectively reduce the thermal conductivity of heat. The air in the pores acts as an insulator, reducing the transfer of heat energy, thereby improving the thermal insulation performance of the material. In addition, the surface structure of ceramsite and perlite can reduce the water absorption of the material and improve its crack resistance.

[0054] 5. The working principle of nano-silicon dioxide

[0055] Principle: Enhanced strength and thermal stability: Nano-silicon dioxide has a high specific surface area and a strong reinforcing effect. In refractory materials, nano-silicon dioxide can not only fill the foam microstructure, but also improve the mechanical properties and thermal stability of the material through its unique nano effect.

[0056] Microscopic mechanism: Nano-silica, as a skeleton material, can form a tight bond with soy protein and other aggregate materials (such as calcined alumina and wollastonite). On a microscopic scale, nano-silica particles enhance the overall strength of the foam structure through physical adsorption or chemical bonding, significantly improving the compressive strength and flexural strength of the material. In addition, the addition of nano-silica effectively improves the thermal stability of the refractory material and reduces the damage to the material caused by thermal stress.

[0057] 6. How does polyvinyl alcohol (PVA) work?

[0058] Principle: Bonding and strengthening: Polyvinyl alcohol (PVA) is a highly adhesive polymer, which is mainly used as a binder in the material to enhance the foam structure and improve the bonding strength. The PVA molecular chain can combine with other materials through hydrogen bonds to form a strong bonding force, thereby enhancing the mechanical properties and fire resistance of the final material.

[0059] Microscopic mechanism: PVA helps improve the bonding properties of refractory materials by forming a strong molecular network structure in cement-based materials. Its molecular chains can be further cross-linked at high temperatures to form a tighter structure, improving the heat resistance, crack resistance and overall strength of the material. PVA can also play a certain auxiliary role in the firing process, reducing the firing temperature and promoting the densification of the material.

[0060] Summary: From the perspective of microscopic mechanism, the role of each raw material is synergistic. The foaming agent forms a stable foam structure, lightweight aggregates (such as expanded perlite and ceramsite) provide thermal insulation, aluminum fluoride promotes sintering and stabilizes the material structure, sodium alginate and PVA enhance the stability and adhesion of the foam, and nano-silicon dioxide improves the mechanical strength and thermal stability of the material. All these microscopic effects work together to form a refractory material with excellent thermal insulation, strength and refractory properties. DETAILED DESCRIPTION

[0061] The exemplary embodiments of the present disclosure will be described in more detail below. Although the exemplary embodiments of the present disclosure are shown below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0062] Example 1 Preparation of high heat-insulating refractory materials for lightweight bricks

[0063] 1. Preparation of soybean protein foaming agent

[0064] 1. Raw materials

[0065] 60 parts of soy protein isolate, 2 parts of red algae polysaccharide (porphyrin), 1 part of glycerol monostearate, 1 part of nano-silicon dioxide.

[0066] 2. Preparation

[0067] Soy protein is extracted using low-temperature hydrolysis technology, and impurities are removed using ultrafiltration technology to obtain high-purity soy protein isolate. Red algae polysaccharide is dissolved in warm water, and stirred and heated to ensure complete dissolution to form a viscous polysaccharide solution to enhance the stability of the foam. Glycerol monostearate is dissolved in a small amount of water and then evenly added to the soy protein and red algae polysaccharide solution to improve the expansibility and stability of the foam. Nano-scale silica powder is added to the protein solution and high-shear mixing is performed to form a uniform nanostructure. These nanoparticles will serve as a skeleton material to provide the necessary strength support inside the foam.

[0068] Air is introduced through high shear stirring, bubble fluidization or ultrasonic technology to form uniform and delicate foam. During the stirring process, the shear stirring speed is 5000rpm, the shear stirring time is 10 minutes, the solution temperature is maintained between 50±5℃, and the pH is adjusted to 7-8 to ensure the best foaming effect of the foaming agent. The foamed solution can be dried at low temperature or vacuum dried to remove excess water. The structural integrity of the foam is maintained by freeze drying technology, and finally the soy protein foaming agent powder is obtained.

[0069] 2. Preparation of high thermal insulation refractory materials for lightweight bricks

[0070] 1. Raw material preparation

[0071] In parts by weight:

[0072] Calcined alumina (Al2O3·xSiO2, particle size <40μm): 30 parts;

[0073] Wollastonite (CaSiO3, particle size <50μm): 25 parts;

[0074] Expanded perlite (particle size <60μm): 15 parts;

[0075] Ceramic granules (particle size <40 μm): 5 parts;

[0076] Soy protein foaming agent (powder, see previous preparation method): 5 parts;

[0077] Sodium alginate solution (concentration 5%): 4 parts;

[0078] Aluminum fluoride (AlF3): 3 parts;

[0079] Hydrated bauxite powder (particle size <40 μm): 8 parts;

[0080] Nano-scale silicon dioxide (SiO2) powder: 3 parts;

[0081] Activated carbon powder: 3 parts;

[0082] Polyvinyl alcohol (PVA): 2 parts;

[0083] Water: appropriate amount.

[0084] 2. Preparation of high thermal insulation refractory materials for lightweight bricks

[0085] (1) Raw material preparation

[0086] Calcined alumina and wollastonite are refractory aggregates that provide high temperature resistance and structural strength. The two are weighed in proportion and dry mixed. Expanded perlite and ceramsite are used as lightweight and heat-insulating materials. After mixing, they are screened into fine particles to ensure uniform particles. The above raw materials are mixed to obtain an aggregate mixture.

[0087] (2) Preparation of foaming solution

[0088] Mix the soy protein foaming agent with water and stir with a stirrer to ensure that the foaming agent is fully dissolved. Add sodium alginate solution (5% concentration) to the foaming agent solution to improve the stability of the foam. Gradually add polyvinyl alcohol (PVA), which acts as a binder to help improve the cohesiveness of the foam. Perform mechanical stirring to introduce air into the solution to form a stable foam and obtain a foaming solution.

[0089] (3) Mixed materials

[0090] Add the foaming solution to the previously prepared aggregate mixture, including calcined alumina, wollastonite, expanded perlite, and ceramsite, and mix all the ingredients evenly by mechanical stirring. Pay special attention to the foam not breaking during the mixing process to ensure the uniform distribution of the foam.

[0091] Aluminum fluoride and hydrated bauxite powder are added during the mixing process, which will promote the sintering process of the material and improve the thermal stability of the final product. Nano-scale silica powder and activated carbon powder are added to further optimize the mechanical strength and thermal insulation properties of the foam.

[0092] (4) Foam molding

[0093] In a well-mixed foam slurry, the stability of the foam is very important. The mixture is poured through a mold, and the foam slurry will naturally take shape in the mold. To ensure the structural stability of the foam, a vibration table can be used to gently vibrate the mold to remove large bubbles and ensure the uniformity of the foam.

[0094] (5) Drying and pre-burning

[0095] Place the cast foam material in a drying room for low-temperature drying (temperature controlled at 70±5℃) to remove excess moisture. The drying time is 6 hours to ensure that the moisture inside the foam is completely evaporated to prevent cracks during the firing process.

[0096] During the pre-firing stage, the dried material is heated to 300°C and kept at a constant temperature for 1 hour to further remove residual moisture and prevent the material from expanding violently at high temperatures.

[0097] (6) High temperature firing

[0098] Firing temperature control: Place the material in a high-temperature furnace for firing. The firing temperature should be controlled between 1280±20℃ and kept constant for 1.5 hours. At this time, the foam will gradually shrink and sinter to form a dense ceramic structure. At the same time, the crystal growth during the sintering process is regulated by the action of aluminum fluoride to avoid cracks.

[0099] Temperature rising process: During the heating process, gradually increase the temperature by 20°C per hour to prevent excessive internal stress in the material due to rapid temperature rise.

[0100] Firing time: According to the specific needs of the material, keep the material sintered at 1350℃ for 2 hours to ensure complete sintering and no cracks.

[0101] Example 2

[0102] Compared with Example 1, the weight ratio of the raw materials is:

[0103] Calcined alumina (Al2O3·xSiO2, particle size <40μm): 35 parts;

[0104] Wollastonite (CaSiO3, particle size <50μm): 20 parts;

[0105] Expanded perlite (particle size <60μm): 18 parts;

[0106] Ceramic granules (particle size <40 μm): 7 parts;

[0107] Soy protein foaming agent (powder, same as in Example 1): 4 parts;

[0108] Sodium alginate solution (concentration 5%): 4.4 parts;

[0109] Aluminum fluoride (AlF3): 4 parts;

[0110] Hydrated bauxite powder (particle size <40 μm): 6 parts;

[0111] Nano-scale silicon dioxide (SiO2) powder: 2.5 parts;

[0112] Activated carbon powder: 3.5 parts;

[0113] Polyvinyl alcohol (PVA): 2.5 parts;

[0114] Water: appropriate amount.

[0115] Example 3

[0116] Compared with Example 1, the weight ratio of the raw materials is:

[0117] Calcined alumina (Al2O3·xSiO2, particle size <40μm): 25 parts;

[0118] Wollastonite (CaSiO3, particle size <50μm): 30 parts;

[0119] Expanded perlite (particle size <60μm): 10 parts;

[0120] Ceramic granules (particle size <40 μm): 10 parts;

[0121] Soy protein foaming agent (powder, same as in Example 1): 7 parts;

[0122] Sodium alginate solution (concentration 5%): 5 parts;

[0123] Aluminum fluoride (AlF3): 5 parts;

[0124] Hydrated bauxite powder (particle size <40 μm): 10 parts;

[0125] Nano-scale silicon dioxide (SiO2) powder: 4 parts;

[0126] Activated carbon powder: 2 parts;

[0127] Polyvinyl alcohol (PVA): 3 parts;

[0128] Water: appropriate amount.

[0129] Comparative Example 1

[0130] Compared with Example 1, no sodium alginate solution was added.

[0131] Comparative Example 2

[0132] Compared with Example 1, no aluminum fluoride is added.

[0133] Comparative Example 3

[0134] Compared with Example 1, no soy protein foaming agent was added.

[0135] Test Example 1

[0136] The performance of the high heat-insulating refractory materials for lightweight bricks prepared in Examples 1-3 and Comparative Examples 1-3 was tested. The test items included bulk density, room temperature compressive strength, flexural strength, thermal conductivity, room temperature water absorption, and refractoriness. The following are the specific test processes and parameters.

[0137] 1. Bulk density

[0138] Bulk density is a measure of the ratio of a material's mass to its volume and is usually calculated using the following formula:

[0139] ρ = M / V;

[0140] Where is the mass of the material and V is the volume of the material. Use a balance and a measuring tool to accurately measure mass and volume.

[0141] Detection process: Take a certain number of samples, weigh their mass, and measure their volume (calculate the volume using the water level method).

[0142] Parameter: Unit: kg / m 3 .

[0143] 2. Compressive strength at room temperature

[0144] Normal temperature compressive strength refers to the ability of a material to withstand pressure at room temperature. It is usually tested using a universal material testing machine.

[0145] Testing process: Loading is carried out according to the standard sample size (40×40×160mm rectangular block) at a loading rate of 0.5MPa / s until the sample is damaged.

[0146] Parameter: The unit is MPa.

[0147] 3. Flexural strength

[0148] Flexural strength testing is used to evaluate the performance of a material when subjected to bending loads.

[0149] Testing process: Take a sample with a size of 40×40×160mm and test it in a three-point bending test. During the test, place the sample on the support point and apply force at a constant loading rate until the sample breaks.

[0150] Parameter: The unit is MPa.

[0151] 4. Thermal conductivity

[0152] Thermal conductivity is the ability of a material to transfer heat and is often measured using a thermal conductivity meter.

[0153] Testing process: Use the laser flash method to measure, keep the sample at a specified temperature for testing, record the heat flow and calculate the thermal conductivity.

[0154] Parameter: The unit is W / (m·K).

[0155] 5. Water absorption rate at room temperature

[0156] Room temperature water absorption is used to measure the ability of a material to absorb water at room temperature.

[0157] Testing process: Dry the sample to constant weight and record its dry weight. Then soak the sample completely in water for 24 hours, take it out and dry it, and then weigh its wet weight. The water absorption rate is calculated by the following formula:

[0158] S=(Wwet−Wdry) / Wdry×100%;

[0159] Among them, Wwet is wet weight and Wdry is dry weight.

[0160] Parameter: The unit is %.

[0161] 6. Refractoriness

[0162] Refractoriness refers to the ability of a material to maintain structural integrity at high temperatures, and is assessed through fire resistance temperature tests.

[0163] Testing process: Place the material in a high-temperature furnace and gradually increase the temperature to the point where the material begins to deform, melt or lose structure, and record this temperature.

[0164] Parameter: The unit is ℃.

[0165] 7. Performance test results

[0166] Table 1 shows the performance test results of the refractory materials prepared in Examples 1-3 and Comparative Examples 1-3.

[0167] Table 1

[0168]

[0169] According to the data in Table 1, we can observe the change of bulk density: the bulk density of Examples 1 to 3 is low, meeting the standard of lightweight bricks. When certain raw materials, such as sodium alginate or soy protein foaming agent, are missing, the bulk density increases, indicating that the material becomes denser, thereby weakening the lightweight property.

[0170] Regarding room temperature compressive strength and flexural strength: Examples 1 to 3 have relatively high compressive strength and flexural strength. In the comparative experiment, when certain raw materials, such as aluminum fluoride or foaming agent, are missing, the strength is reduced. This shows that foaming agent and aluminum fluoride have a significant effect on improving the strength of the material.

[0171] Thermal conductivity: Thermal conductivity decreases with increasing proportions of foaming agent and lightweight aggregate (e.g. expanded perlite). In the absence of foaming agent or other lightweight materials, thermal conductivity increases, indicating a decrease in thermal insulation performance.

[0172] Water absorption: Water absorption increases in the absence of a blowing agent. Normally, a material's reduced water absorption means it is more compact, but in this application this can have a detrimental effect on insulation performance and long-term stability.

[0173] Refractoriness: Refractoriness is closely related to firing temperature. The refractoriness of Examples 1 to 3 is relatively high, but when certain additives, such as aluminum fluoride, are lacking, the refractoriness will decrease slightly, which may lead to reduced stability of the material in a high temperature environment.

[0174] In summary, the refractory materials of Examples 1-3 all show excellent performance in terms of lightness, strength, thermal insulation and refractoriness. In particular, by adjusting the ratio of foaming agent and lightweight aggregate, the bulk density and thermal conductivity of the material can be effectively controlled, thereby achieving an ideal lightweight thermal insulation effect. At the same time, the addition of aluminum fluoride plays a key role in improving the compressive strength and refractoriness of the material. Therefore, in order to prepare a refractory material with excellent performance, it is crucial to select a suitable raw material ratio and auxiliary agent. In practical applications, the formula should be adjusted according to specific needs to achieve the best comprehensive performance.

[0175] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a highly heat-insulating refractory material for lightweight bricks, characterized in that: include: Mixing calcined alumina, wollastonite, expanded perlite and ceramsite to obtain an aggregate mixture; After dissolving the soy protein foaming agent, sodium alginate and polyvinyl alcohol are added, and the foaming solution is obtained after stirring; The foaming solution and the aggregate mixture are mixed and stirred, and aluminum fluoride, hydrated bauxite powder, nano-scale silicon dioxide powder and activated carbon powder are added during the stirring process, and the foam slurry is obtained after stirring evenly; The foam slurry is cast and then dried at low temperature, and then subjected to constant temperature treatment at 300±20° C. to obtain a material to be fired; Firing the material to be fired to obtain the high heat-insulating refractory material for lightweight bricks; The weight ratio of the calcined alumina, wollastonite, expanded perlite, ceramsite, soybean protein foaming agent, sodium alginate, aluminum fluoride, hydrated bauxite powder, nano-scale silicon dioxide, activated carbon powder and polyvinyl alcohol is 25-35:20-30:10-18:5-10:4-7:4-5:3-5:6-10:2.5-4:2-3.5:2-3; The preparation method of the soy protein foaming agent comprises: dissolving red algae polysaccharide in water to obtain a polysaccharide solution; After mixing the soy protein and the polysaccharide solution, glycerol monostearate is added, and after mixing evenly, nano-scale silicon dioxide powder is added for shear mixing to obtain the soy protein foaming agent; The weight ratio of the soybean protein, red algae polysaccharide, glycerol monostearate and nanometer silicon dioxide powder is 50-70:1-3:1-2:0.5-2.

2. The method for preparing a highly heat-insulating refractory material for lightweight bricks according to claim 1, characterized in that: During the shear mixing, the shear speed is 3000-6000 rpm, the shear time is 3-10 minutes, and the solution temperature is 40-60°C.

3. The method for preparing a highly heat-insulating refractory material for lightweight bricks according to claim 1, characterized in that: The red algae polysaccharide is laver.

4. The method for preparing a highly heat-insulating refractory material for lightweight bricks according to claim 1, characterized in that: When the material to be fired is fired, the firing temperature is 1250-1350°C.

5. A high heat-insulating refractory material for lightweight bricks, characterized in that: The high thermal insulation refractory material for lightweight bricks is prepared according to the method for preparing the high thermal insulation refractory material for lightweight bricks according to any one of claims 1 to 4.

6. Use of the high heat-insulating refractory material for lightweight bricks according to claim 5 in the preparation of refractory building materials.

Citation Information

Patent Citations

  • Alumina light-weight brick and preparation method thereof

    CN101708997A

  • Production technology of light-weight and heat-insulation brick

    CN105801064A

  • Building insulation material and preparation method thereof

    CN109133819A

  • Food foaming agent and preparation method thereof

    CN115251360A

  • Multicomponent adjuvant for combustion and method for producing calcium aluminate using same

    CN1807249A